Anthony's textbook of anatomy & physiology - Patton, Kevin T.; Thibodeau, Gary A. (Singapore : Elsevier Science, 2009)
An introductory text on human form and function. It focuses on concepts rather than just descriptions to help students unify information and explains the body's homeostatic regulation. It contains many practical features and hundreds of illustrations. It also features critical thinking learning opportunities.
UNIT ONE: The Body as a Whole -- UNIT TWO: Support and Movement -- UNIT THREE: Communication, Control, and Integration -- UNIT FOUR: Transportation and Defense -- UNIT FIVE: Respiration, Nutrition, and Excretion -- UNIT SIX: Reproduction and Development.
Keywords: HUMAN ANATOMY